Trochleaectomy: An Effective Treatment of Trochlear Pain in Monocular Patients. Issue 2 (June 2021) - Mettu, Pradeep; Mancini, Ronald; Friedman, Deborah I.; Garrity, James A.
Abstract : Background: Conventional treatment options for trochlear pain arising from trochleitis or primary trochlear headache include oral anti-inflammatory medications and/or local injection of corticosteroids and local anesthetic. Trochleaectomy is an additional option to consider for monocular patients with intractable trochlear pain. Methods: We report 3 patients undergoing trochleaectomy for refractory trochlear pain syndromes. Results: Trochleaectomy resulted in resolution of their periocular discomfort. Conclusions: Trochleaectomy is an effective procedure to treat trochlear pain syndrome in functionally monocular patients.